A comparative questionnaire study of patient complaint levels between magnetostrictive ultrasonic scaler (Cavitron®) and piezoelectric ultrasonic scalers. Issue 3 (2nd December 2020) - Ikeda, Yuichi; Kawada, Ayako; Tanaka, Daiki; Ikeda, Eri; Kobayashi, Hiroaki; Iwata, Takanori
Abstract: Objectives: Ultrasonic scalers often cause an uncomfortable feeling to patients during the procedure. This study was conducted to compare patient complaint levels between magnetostrictive (M‐USSC) and piezoelectric ultrasonic scalers (P‐USSC) during supragingival scaling. Methods: This study enrolled 82 subjects who received supportive periodontal therapy for at least 2 years. At each recall visit, probing pocket depth (PPD), bleeding on probing (BOP) and O'Leary plaque control record (O'PCR) were recorded. Then, supragingival scaling was performed using P‐USSC (Varios or Petit Piezo) at the first visit and M‐USSC (Cavitron) at the second visit. After each treatment, a questionnaire survey was performed using the Wong‐Baker Faces Pain Scale for six items, which included the typical complaints occurring during ultrasonic scaling. Results: The scores for all the six items related to patient complaints were greater for P‐USSC than for M‐USSC ( p < 0.001). Patient complaints such as discomfort, pain, sound, vibration, hyperesthesia and length of treatment time were ameliorated in 74%, 65%, 80%, 67%, 57% and 53% of subjects using M‐USSC, respectively. On the other hand, only <5% of subjects showed deterioration in terms of each complaint. Conclusion: This study suggested that M‐USSC causes fewer patient complaints during supragingival scaling than P‐USSC. M‐USSC may improve patient motivation and compliance and may contribute towards achieving successful treatment outcomes. However, this result could differ depending on the shape of the tip and the insert and treatment site. Further research will be required under various conditions.